Ultra-widefield color fundus photography combined with high-speed ultra-widefield swept-source optical coherence tomography angiography for non-invasive detection of lesions in diabetic retinopathy - Li, Jie; Wei, Dingyang; Mao, Mingzhu; Li, Mengyu; Liu, Sanmei; Li, Fang; Chen, Li; Liu, Miao; Leng, Hongmei; Wang, Yiya; Ning, Xinru; Liu, Yi; et al. (Frontiers in Public Health, 2022)
Purpose: To compare the detection rate of diabetic retinopathy (DR) lesions and the agreement of DR severity grading using ultra-widefield colour fundus photography (UWF CFP) combined with high speed ultra-widefield swept-source optical coherence tomography angiography (UWF SS-OCTA) or fluorescein angiography (FFA). Methods: This prospective, observational study recruited diabetic patients who had already taken FFA examination from November 2021 to June 2022. These patients had either no DR or any stage of DR. All participants were imaged with a 200° UWF CFP and UWF SS-OCTA using 24×20mm scan model. Images were independently evaluated for the presence or absence of DR lesions including microaneurysms (MAs), intraretinal hemorrhage (IRH), non-perfusion areas (NPAs), intraretinal microvascular abnormalities (IRMAs), venous beading (VB), neovascularization elsewhere (NVE), neovascularization of the optic disc (NVD) and vitreous or preretinal hemorrhage (VH/PRH). Agreement of DR severity grading based on UWF CFP plus UWF SS-OCTA and UWF CFP plus FFA was compared. All statistical analyses were performed using SPSS V.26.0. Results: One hundred and fifty-three eyes of 86 participants were enrolled in the study. The combination of UWF CFP with UWF SS-OCTA showed similar detection rate compared with UWF CFP plus FFA for all the characteristic DR lesions (p>0.05), except NPAs (p=0.039). Good agreement was shown for identification of VB (κ=0.635), and very good agreement for all the rest DR lesions between the two combination methods (κ value ranged from 0.858 to 0.974). When compare the grading of DR severity, very good agreement was achieved between UWF CFP plus UWF SS-OCTA and UWF CFP plus FFA (κ=0.869). Conclusion: UWF CFP plus UWF SS-OCTA had very good agreement in detecting DR lesions and determining the severity of DR compared with UWF CFP plus FFA. This modality has the potential been used as a fast, reliable and non-invasive method for DR screening and monitoring in the future.